Indonesian Image of the Ottoman Caliphate and the New Republic of Türkiye 1918–1925 - Özay, Mehmet; Deliana, Nia (Studia Islamika, 2024)
This article is a preliminary study on Indonesians’ perceptions on the decline of the Ottoman Caliphate, and the rise of the Turkish Republic based on the highlights in vernacular press printed in Java and Sumatra. By scrutinizing textual discourse on the Caliphate and the Turkish Republic, this paper examined Indonesians’ views delivered in newspapers, such as Poestaka Hizboel Wathan, Medan Prijaji, Soeara Islam, Zaman Baroe, and Bintang Islam. These newspapers informed on the consecutive political changes, including a total ‘weltanschauung’ during the ruling era of Mustafa Kemal, which drew the significant attention of Indonesian readers, contradictory responses on the complexities of the developments among the intellectuals. Through qualitative methodology and content analysis, this paper gives additional contribution to the study of historical relations between Indonesia and Türkiye.